Sarcopenia in children with chronic liver disease: Prevalence and impact on liver transplant outcomes - Veraldi, Silvio; Pietrobattista, Andrea; Soglia, Giovanna; Monti, Lidia; Alterio, Tommaso; Mosca, Antonella; Liccardo, Daniela; Basso, Maria Sole; Della Corte, Claudia; Russo, Luca; Candusso, Manila; Chiusolo, Fabrizio; et al. (Frontiers in Pediatrics, 2022)
Sarcopenia is a clinical condition characterized by a reduction in muscle mass, which typically affects adult patients; however, it has recently been recognized in pediatric literature. Few studies in children with chronic liver disease (CLD) undergoing liver transplantation (LT) have investigated the role of sarcopenia, with controversial results. The aim of our study was to assess the prevalence and impact of sarcopenia among children with CLD who are candidates for LT. We conducted a retrospective, single-center study at Bambino Gesù Children’s Hospital (Rome, Italy) from July 2016 to July 2021, evaluating all children (0–16 years old) with CLD listed for LT with an abdomen computed tomography imaging available before LT. The total psoas muscle surface area (t-PMSA) was defined as the sum of left and right psoas muscle surface area measured at L4–L5 on axial images. The t-PMSA z-score was calculated according to reference data, and sarcopenia was defined as a t-PMSA z-score of ≤-2 (1–16 years) or a psoas muscle index (PMI; PMI=tPMSA/(100 x BSA) ) of <50th percentile of the population examined (<1 year). Clinical, laboratory, and LT outcome data were collected from all the patients with CLD. 27 out 48(56%) of the patients aged 1–16 years were sarcopenic. No differences were noted in anthropometrics, nutritional support, liver function tests, model for ESLD (MELD), or pediatric ESLD (PELD) scores between patients with and without sarcopenia. The former showed a higher prevalence of respiratory complications (66.7% vs. 42.1%) and need for inotropes (40.7% vs. 10.8%) after LT. Among patients aged 0-1 years (n: 36), those with reduced muscle mass (50%) had a longer hospitalization time (44 vs. 24 days) and higher incidences of multi-organ failure syndrome (38.9% vs. 0%) and intensive care unit-related infections (61.1% vs. 27.8%) compared to those with greater muscle mass. t-PMSA and PMI were statistically significant predictors of LT outcomes. Sarcopenia is a reliable index of frailty in children with CLD, as its presence is associated with the risk of a more challenging LT. Future studies will have to investigate the functional aspects of sarcopenia and conceive preventive measures of muscle wasting in CLD patients.